Media election survey referendum 1980 - News analysis - Asp, Kent (University of Gothenburg, 1986)
This is the second study of the political contents in press, radio and television within the research projects ´Mass media and the electorate´ and ´Swedish election campaign´ and it was carried out in connection with the referendum on nuclear power in March 1980. It is a detailed campaign study of news reporting in the press, radio and television during the last ten weeks before the day of the referendum.

Purpose:

To describe, identify and analyse media's reporting of the election campaign 1980.

I samband med valet 1979 genomfördes vid Statsvetenskapliga institutionen, Göteborgs universitet en större studie av det politiska innehållet i press, radio och TV. Syftet med studien var att besvara frågeställningar kring massmediernas innehåll och effekter.

I samband med folkomröstningen om kärnkraft i mars 1980 genomfördes den andra studien i serien. Undersökningen innehåller dels en detaljerad kampanjstudie över de nyhetsrapporter som förekom i tryckt press, tv och radio under de tio sista veckorna före valdagen. Den andra delen av undersökningen utgörs av en analys av tidningarnas ledarmaterial och televisionens övriga programutbud under tioveckorsperioden.

Syfte:

Att beskriva, kartlägga och analysera nyhetsmedias rapportering av valrörelsen 1980.
Medievalundersökningen folkomröstningen 1980 - Nyhetsanalysen
Keywords: elections; val; mass media; massmedia; politics; politik; mass media exposure; massmediaexponering; newspaper press; nyhetspress; election broadcasting; valbevakning i tv och radio; radio news; radionyheter; news; nyheter; television news; tv-nyheter; news flow; nyhetsflöde; internal politics; inrikespolitik; party politics; partipolitik; politicians; politiker; press; press; mass media coverage; massmediabevakning; Media; Media; Energy and natural resources; Energi och naturresurser; Elections; Val; Political ideology; Politisk ideologi; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap